Combining citizen science data and literature to build a traits dataset of Taiwan’s birds - Shu-Wei Fu; Meng-Chieh Feng; Po-Wei Chi; Tzung-Su Ding (Scientific Data, 2024)
Abstract Trait-based methodologies are gaining traction in the field of ecology, providing deeper insights into ecosystem structure and functions. To this end, trait databases tailored to specific taxonomic groups have become foundational. In Taiwan, the collaborative efforts of avian researchers and dedicated citizen scientists have led to the compilation of a vast array of data. This includes web-sourced images from social media, spatial distribution records from eBird, and morphological metrics from banded birds and specimens. Enriched by peer-reviewed literature, we have meticulously assembled a comprehensive trait dataset encompassing 454 bird species across 73 families. This dataset covers a wide range of traits, including foraging ecology, morphological characteristics, territorial behaviors, breeding attributes, and the roles of bird species in ecosystem regulation. As an invaluable resource, this dataset lays the foundation for in-depth exploration of functional diversity, trait-based community ecology, ecosystem function, and critical insights needed to shape conservation strategies.